Contesting household debt in Croatia: the double movement of financialization and the fetishism of money in Eastern European peripheries - Mikuš, Marek (Dialectical Anthropology, 2019)
Croatia has experienced a marked boom in household debt in the 2000s. Much of this lending took high-risk and predatory forms that transferred significant risks to debtors, which in turn became the target of contestation by debt activists. This paper uses the Polanyian idea of "double movement" to show how the Croatian debt contestations responded to the distinctively peripheral form of financialization in Eastern Europe, characterized by unequal geoeconomic relationships and an intensified expropriation of debtors. This framework further highlights the importance of money in contemporary credit/debt relationships and their contestation, which has so far received insufficient attention in relevant anthropological scholarship. Instead of the currently fashionable credit theories of money, the paper uses the Marxian concept of the fetishism of money to unpack the roles of money in these processes. The analysis of discourses and practices of two groups of debtors and activists reveals how they used nationalist ideological frameworks and institutional channels such as litigation, again largely ignored by existing anthropological literature, to challenge the particular inequalities of peripheral financialization and the expropriation of debtors through the lenders' predatory manipulations of the money fetish.
Anthropology
Keywords: Croatia; Eastern Europe; consumer credit; contestation; debtor & creditor; financialization; household debt; money

Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Anthropology; Political Science
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy